Thermochronological evolution of the Eastern Pontides and the Eastern Anatolian Plateau and NW Lesser Caucasus (Turkey, Georgia, Armenia) - Albino, Irene <1985> (Alma Mater Studiorum - Università di Bologna, 2013)
The analysis of apatite fission tracks is applied to the study of the syn- and post-collisional thermochronological evolution of a vast area that includes the Eastern Pontides, their continuation in the Lesser Caucasus of Georgia (Adjara-Trialeti zone) and northern Armenia, and the eastern Anatolian Plateau. The resulting database is then integrated with the data presented by Okay et al. (2010) for the Bitlis Pütürge Massif, i.e. the western portion of the Bitlis-Zagros collision zone between Arabia and Eurasia. The mid-Miocene exhumation episode along the Black Sea coast and Lesser Caucasus of Armenia documented in this dissertation mirrors the age of collision between the Eurasian and Arabian plates along the Bitlis suture zone. We argue that tectonic stresses generated along the Bitlis collision zone were transmitted northward across eastern Anatolia and focused (i) at the rheological boundary between the Anatolian continental lithosphere and the (quasi)oceanic lithosphere of the Black Sea, and (ii) along major pre-existing discontinuities like the Sevan-Akera suture zone.The integration of both present-day crustal dynamics (GPS-derived kinematics and distribution of seismicity) and thermochronological data presented in this paper provides a comparison between short- and long-term deformation patterns for the entire eastern Anatolia-Transcaucasian region. Two successive stages of Neogene deformation of the northern foreland of the Arabia-Eurasia collision zone can be inferred. (i) Early and Middle Miocene: continental deformation was concentrated along the Arabia-Eurasia (Bitlis) collision zone but tectonic stress was also transferred northward across eastern Anatolia, focusing along the eastern Black Sea continent-ocean rheological transition and along major pre-existing structural discontinuities. (ii) Since Late-Middle Miocene time the westward translation of Anatolia and the activation of the North and Eastern Anatolian Fault systems have reduced efficient northward stress transfer.